Chair - Parmaxi, Antigoni (My University, 2026)
The event under the title ‘Needs, challenges and experiences of women in STEM: Best practices from Higher Education and the Industry’ uncovered the needs and challenges of women in the field of STEM in Higher Education and the Industry. The event provided information on the work conducted in the FeSTEM project and we will also launch a discussion on the needs and challenges of women in STEM in industry and academia. Keynote Speaker: Androulla Vasiliou, Former European Commissioner for Education, Culture, Multilingualism & Youth